Implementasi Paradigma Mutu Madrasah dalam Perspektif Al-Qur’an : Studi Lapangan di MIS Al-Hunafa Palangka Raya - Weny Windasari; Triwid Syafarotun Najah; Dakir Dakir (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to analyze the implementation of the madrasah quality paradigm from the perspective of the Qur'an at MIS Al-Hunafa Palangka Raya. The study used a qualitative field research approach with observation, interview, and documentation techniques. Data analysis used the Miles and Huberman model. The results of the study indicate that: 1) the quality paradigm is understood not only to be oriented towards academics, but also to the formation of character and spiritual values ​​of students; 2) the implementation of the quality paradigm is carried out through the integration of Qur'anic values ​​such as amanah, itqan, ihsan, discipline, and responsibility in madrasah culture, learning, and religious activities; and 3) the implementation of quality still faces obstacles in the form of limited infrastructure, variations in teacher competencies, and technological demands, so that the madrasah carries out strengthening through teacher training, facility optimization, and the development of a quality culture based on Qur'anic values. Thus, the implementation of the quality paradigm at MIS Al-Hunafa has been running quite well and is carried out sustainably.